Standardization of Midwifery Education in Efforts to Improve Professionalism in Midwifery Services in Indonesia - Klanting Kasiati (Health Notions, 2018)
Midwives are part of one health worker who has a strategic role in health development in Indonesia, so that standardized preparation efforts are needed since their education. In connection with the above, continuously efforts have been made to standardize the implementation of midwifery education in Indonesia, which in turn aims to produce midwives who are truly ready to play a role in playing a role in health development especially maternal and child health. Keywords: Midwifery, Education, Standardization, Indonesia